A solution to the hot cracking problem for aluminium alloys manufactured by laser beam melting. (15th September 2020) - Opprecht, Mathieu; Garandet, Jean-Paul; Roux, Guilhem; Flament, Camille; Soulier, Mathieu
Abstract: A method to eliminate hot cracking phenomena for aluminium alloys in Laser Beam Melting (LBM) is presented in this paper, focused here on the 6061 alloy. 6061 is a precipitation-hardened aluminium alloy, containing magnesium and silicon as its major alloying elements. This alloy, commonly used in the aeronautic and automotive industries, thanks to its excellent weight to strength ratio and high thermal conductivity, is particularly prone to hot cracking, in particular during LBM processing. The solution to remove cracks proposed in the present paper is to induce grain refinement to avoid the development of large columnar structures. To this end, various quantities of Yttrium Stabilized Zirconia (YSZ) are added to an Al6061 base powder using a dry mixing (Turbula Ⓡ ) procedure. Experiments highlight a grain refinement effect depending on the added YSZ quantity. From 1 vol% on, SEM and EBSD images reveal an equiaxed-columnar bimodal grain microstructure. Results show that the addition of 2 vol% YSZ allows to fully avoid cracks due to a continuous equiaxed band at melt pool boudaries. Additionally, TEM and DRX investigations provide new insights into the becoming of added particles along the printing process. The experimental results are then discussed on the basis of a number of existing solidification models, with a focus on the necessary conditions for the establishment of an equiaxed solidification regime. Graphical abstract: Image, graphical abstract